Determinan Kinerja Sektor Publik: Dimoderasi Sistem Pengendalian Interen pada Puskesmas BLUD di Kota Pekanbaru - Mai Siska; Ria Nelly Sari; Yesi Mutia Basri (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2021)
This research is the result of an empirical study that shows facts in explaining the properties that occur in the object under study through statistical principles. The purpose of this study was to examine and analyze the factors that influence the performance of regional public health service agencies in the city of Pekanbaru such as financial management of regional public service agencies, quality of human resources and utilization of information systems with internal control as moderating variables. The object of this research is all public health centers of regional public service agencies which is in the city of Pekanbaru. The results showed that the financial management of regional public service agencies, the quality of human resources , and the use of information systems had a positive effect on the performance of public health centers and was strengthened by the presence of internal controls. This research has implications for public sector organizations that implement financial management of regional public service agencies such as community health centers as motivation and evaluation materials related to performance achievement through the process of improving the financial management of regional public service agencies, the quality of human resources , utilization of information systems and internal control. Keywords: Financial Management of regional public service agencies, quality of human resources, utilization of information systems, organizational performance of local public service agencies